Image processing and acquisition using Python - Chityala, Ravishankar; Pudipeddi, Sridevi (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
"Image Processing and Acquisition using Python provides readers with a sound foundation in both image acquisition and image processing--one of the first books to integrate these topics together. By improving readers' knowledge of image acquisition techniques and corresponding image processing, the book will help them perform experiments more effectively and cost efficiently as well as analyze and measure more accurately. Long recognized as one of the easiest languages for non-programmers to learn, Python is used in a variety of practical examples.A refresher for more experienced readers, the first part of the book presents an introduction to Python, Python modules, reading and writing images using Python, and an introduction to images. The second part discusses the basics of image processing, including pre/post processing using filters, segmentation, morphological operations, and measurements. The last part describes image acquisition using various modalities, such as X-ray, CT, MRI, light microscopy, and electron microscopy. These modalities encompass most of the common image acquisition methods currently used by researchers in academia and industry"--
"If title belongs to a series, the exact series title that will appear in the book is: Series number, exactly as it will appear in the book: Will the first-named author listed in Author Information appear as the first-named author for all other volumes of the series? "--
Includes bibliographical references (pages 341-350) and index.
Keywords: Image processing; Python (Computer program language); TECHNOLOGY & ENGINEERING / Biomedical; TECHNOLOGY & ENGINEERING / Imaging Systems; MATHEMATICS / Graphic Methods